2018
DOI: 10.3390/soc8030062
|View full text |Cite
|
Sign up to set email alerts
|

The Remains of the Socialist Legacy: The Influence of Socialist Socialization on Attitudes toward Income Inequality

Abstract: Despite convergence processes between Western and post-socialist societies in the past three decades, there are still considerable cross-country differences in individuals’ attitudes toward income inequality. To explain these differences, studies have primarily focused on the role of macro level differences and have only theoretically acknowledged how the role of diverging socialization experiences could also be responsible. To date, little is known about the importance of socialization for attitudes toward in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Perceived Economic Inequality in Everyday Life (PEIEL) are the daily experiences in which individuals perceive differences in the way resources are distributed between the members of a society (García-Castro, . From this perspective, experience is the basis on which individuals evaluate inequality (Ignácz, 2018).…”
Section: Perceived Economic Inequality In Everyday Life Tolerance Tomentioning
confidence: 99%
“…Perceived Economic Inequality in Everyday Life (PEIEL) are the daily experiences in which individuals perceive differences in the way resources are distributed between the members of a society (García-Castro, . From this perspective, experience is the basis on which individuals evaluate inequality (Ignácz, 2018).…”
Section: Perceived Economic Inequality In Everyday Life Tolerance Tomentioning
confidence: 99%
“…With additional evidence about the power of socialization, Ignácz [98] finds notable cross-country differences between Western and post-socialist societies in individuals' attitudes toward income inequality, even three decades after the end of the Cold War. Applying an adapted age-period-cohort analysis on the dataset of the 1992, 1999, and 2009 waves of the ISSP's Social Inequality module, Ignácz demonstrates that socialization has a substantial effect on attitudes and that socialist socialization clearly differentiates individuals from post-socialist countries from those from the West.…”
Section: Socialization Effectsmentioning
confidence: 99%
“…Indeed, Ignácz (2018) found that the more of a person’s formative years were spent under communism, the more that person was likely to endorse the social values championed by communism, such as social equality as a public good that is to be provided by government. 1 By contrast, if a person had not spent much time under communist rule, they tended to be less likely to endorse the same kind of principles even if they were from a post-communist nation (see also Pop-Eleches & Tucker, 2019).…”
Section: Equality Concernsmentioning
confidence: 99%
“…Frequently, these differences between post-communist and non-communist European countries center on attitudes toward equality, especially for older people in former post-communist countries. That is, people who spent a significant, if not all of their formative years under communist rule, tend to be much more sensitive to societal inequality compared to their younger counterparts and people of all ages elsewhere in Europe (e.g., Ignácz, 2018). With there being stark differences in societal inequality across countries, this begs the question to what extent inequality shapes people’s outlook on their society and their well-being.…”
mentioning
confidence: 99%